Lighthouse Parenting Programme: Description and pilot evaluation of mentalization-based treatment to address child maltreatment. (October 2019) - Byrne, Gerry; Sleed, Michelle; Midgley, Nick; Fearon, Pasco; Mein, Clare; Bateman, Anthony; Fonagy, Peter
This article introduces an innovative mentalization-based treatment (MBT) parenting intervention for families where children are at risk of maltreatment. The Lighthouse MBT Parenting Programme aims to prevent child maltreatment by promoting sensitive caregiving in parents. The programme is designed to enhance parents' capacity for curiosity about their child's inner world, to help parents 'see' (understand) their children clearly, to make sense of misunderstandings in their relationship with their child and to help parents inhibit harmful responses in those moments of misunderstanding and to repair the relationship when harmed. The programme is an adaptation of MBT for borderline and antisocial personality disorders, with a particular focus on attachment and child development. Its strength is in engaging hard to reach parents, who typically do not benefit from parenting programmes. The findings of the pilot evaluation suggest that the programme may be effective in improving parenting confidence and sensitivity and that parents valued the programme and the changes it had helped them to bring about.